Communicating knowledge - Bedford, Denise; Chalphin, Ira; Dietz, Karen; Phlypo, Karla (Emerald Publishing Limited, 2022)
The communication of knowledge is a core concept in the field of knowledge management and an essential new role and responsibility of business managers. Knowledge capital is the primary source of wealth and the key source of productivity in the knowledge economy. Stockpiling and storing knowledge diminishes its value. It is only through circulation that our knowledge capital realizes its business value. Communicating Knowledge addresses essential management practices in the 21st-century knowledge economy. It speaks to the change that every organization is experiencing as they transition from an industrial to a knowledge organization. The COVID-19 pandemic has heightened an awareness of communications practices in the past year, with communication norms and behaviors being challenged at every level. How we communicate, when we communicate, with whom we communicate, and what we communicate is currently undergoing a global reform. Communication competencies are no longer desirable qualities in managers - they are essential. This book is intended for business managers working at all levels, knowledge management practitioners and scholars, communications professionals, practitioners, and consultants.
Includes index.
Keywords: Knowledge management.; Communication in management.; Business & Economics -- Information Management.; elektronické knihy; electronic books